Tenderness and cooking characteristics of beef cooked by electric belt grill, forced-air convection oven, or electric broiler - Lawrence, T.E.; King, D.A.; Obuz, E.; Yancey, E.J.; Dikeman, Michael E. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
We used an electric belt grill, a forced-air convection oven, and an electric broiler to cook 170 bottom round, 142 brisket, 177 top sirloin, 176 strip loin, and 136 eye of round steaks from USDA Select carcasses to determine the effects of cooking method and muscle on shear force values, cooking traits, and repeatability of duplicate measurements. All cooking treatments allowed differences to be detected (P<0.05) in Warner-Bratzler shear force, although the differences were inconsistent. Shear force values of strip steaks and eye of round steaks were similar across cooking treatments; however, shear force values of bottom round, brisket, and top sirloin steaks were different (P<0.05) among cooking treatments. Based on poor repeatability, shear force values for top sirloin steaks appear unreliable. Poor repeatability for shear force values from steaks cooked by the forced-air convection oven are a result of drastic temperature changes that occur when the doors are opened to remove steaks. We do not recommend using a forced-air convection oven to test treatment effects on shear force values when cooking multiple steaks simultaneously. Belt grill cooking resulted in the highest shear force repeatability R = 0.07 to 0.89) of strip steaks. Electric broiling resulted in acceptable R = 0.60) repeatability of shear force measurements for all classes of steaks. The electric broiler and electric belt grill are both satisfactory cooking methods when measuring shear force of bottom round, brisket, strip loin, and eye of round steaks.
Keywords: Beef; Cooking; Repeatability; Tenderness